Lymphocytes from Peyer’s Patches and Mesenteric Lymph Nodes Proliferation in a Model of Oral and Systemic Sensitization with Ovalbumin - Miguel Vinuesa; Norberto Bassan (Journal of Pharmacy and Nutrition Sciences, 2013)
Background: In previous works we demonstrated that subcutaneous sensitization with Ovalbumin (OVA) induce generation of specific IgE antibodies and modifications of immune cells populations in different mucosal sites in rabbit. The aim of the study was the evaluation of OVA specific lymphoproliferation in mesenteric lymph nodes (MLNs), spleen and Peyer’s patch from OVA orally and subcutaneous sensitized and challenged rabbits. Methods: New Zealand white rabbits were divided into six groups: G1 (n=8): orally sensitized and challenged with OVA; G2 (n=10): subcutaneous sensitized with OVA and oral challenged (OVA); G3 (n=10): subcutaneous sensitized and oral challenged with PBS (phosphate buffer saline). G4-G5 and G6 (n=9 each) controls. Four hours after challenge animals were sacrificed and obtained samples were processed for lymphoproliferation studies: isolated cells from MLNs, spleen and Peyer’s patch from the different groups were suspended in culture media containing OVA or Concanavaline A and were cultured for 48, 72 and 120 hours. Proliferation was measured as incorporation of radioactive element as counts per minute (CPM). Results: Spleen derived lymphocytes showed important proliferation at subcutaneous sensitized groups when incubated with OVA. Meanwhile, proliferation was significantly higher in lymphocytes originated in MLNs from subcutaneous OVA sensitized and oral challenged rabbits at 48, 72 and 120 hours of incubation. No significant proliferation was observed in Peyer’s Patch derived lymphocytes. Conclusions: We conclude that proliferation of OVA-specific spleen originated lymphocytes was successful after systemic sensitization but after oral challenge with the antigen, only OVA incubated MLNs-originated lymphocytes showed proliferation as compared with Peyer’s patch. This fact evidence a main participation of MLNs in this model of food allergy.